An additional impact mechanism for hitting the ball toward the opposite field in baseball - Kidokoro,S.; Yanai, T. (Japan Journal of Physical Education, Health and Sport Sciences, 2015)
In baseball, batters occasionally aim to hit the ball toward the opposite field. Players and coaches generally believe that the impact surface of the bat needs to face toward the opposite field at the instant of ball impact, so that the ball makes an oblique impact with the bat and bounces off toward the opposite field. Photograms and video recordings of opposite-field hitting, however, often give an impression that the impacting surface of the bat does not necessarily face toward the opposite field. Therefore, there may be an overlooked mechanism for opposite-field hitting. The purpose of this study was to examine the kinematic parameters of ball impact that determine the direction of the struck ball in opposite-field hitting. Sixteen collegiate baseball players performed ten trials of opposite-field hitting, and the movements of the ball and bat before, at, and after impact were recorded with three high-speed cameras (1000 fps) for three-dimensional analysis. The projection angles of the bat on the horizontal plane (horizontal bat angle), the vertical plane (vertical bat angle) and the angle from horizontal of the line of impact (line of impact angle) were determined at the instant of ball impact. The struck ball travelled toward the opposite field at 23.0±7.5° from the center line of the field. Whereas the mean value of the horizontal bat angle was 6.7° toward the opposite field, the bat was facing towards the center and the same field in 16.4% of all trials. These results indicate that the batter can hit the ball toward the opposite field even if the impact surface of the bat is facing toward the center or the same field at the instant of ball impact. In this paper, we reveal an additional mechanism for hitting the ball toward the opposite field.